2018
DOI: 10.1371/journal.pbio.2005317
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid starvation sensing dampens IL-1β production by activating riboclustering and autophagy

Abstract: Activation of the amino acid starvation response (AAR) increases lifespan and acute stress resistance as well as regulates inflammation. However, the underlying mechanisms remain unclear. Here, we show that activation of AAR pharmacologically by Halofuginone (HF) significantly inhibits production of the proinflammatory cytokine interleukin 1β (IL-1β) and provides protection from intestinal inflammation in mice. HF inhibits IL-1β through general control nonderepressible 2 kinase (GCN2)–dependent activation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…As expected following the undocking of mTOR from the lysosomes and in line with recent works [39,41], we observed the induction of ATG by HF in all the analyzed cell lines. On long term sustained AAR and autophagy, as induced by HF, led to apoptosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As expected following the undocking of mTOR from the lysosomes and in line with recent works [39,41], we observed the induction of ATG by HF in all the analyzed cell lines. On long term sustained AAR and autophagy, as induced by HF, led to apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we found that HF initially induces autophagosome formation and later impairs the autophagosome-lysosome fusion step, much alike chloroquine. Of note, our work is the first to show a dual-effect of HF on autophagy as the other studies investigating HF-induced autophagy reported only the induction of autophagy by the HF and not an impairment of the autophagosome-lysosome fusion step [39,41]. We hypothesize that the effect of HF on the autophagosomelysosome fusion step may differ depending on the cell line, HF concentration and incubation time.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Surprisingly, the levels of phospho-eIF2α were not altered, except under UV-stress in GCN2 depleted cells, where it was abolished. Furthermore, GCN2 was shown to induce autophagy that clear the SG (Battu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Later, cells were washed gently with ice‐cold 1XPBS and lysed in lysis buffer (20 mM HEPES,150 mM NaCl, pH 7.5, 1% Triton‐X 100, 100 mM NaF, 1 mM EDTA, 17.5 mM β‐glycerophosphate, 10% glycerol, 1mM phenyl methyl sulphonyl fluoride, 2 mg/mL pepstatin, and 4 mg/mL aprotinin, supplemented with protease inhibitor cocktail tablets (Sigma–Aldrich) were added dropwise to cells on culture dish. Cells were incubated on ice for 30 min in cell lysis buffer with occasional vortexing as described earlier . Cells were scraped and lysed in cell lysis buffer.…”
Section: Methodsmentioning
confidence: 99%